La defensa de la ciudad de Valencia 1936-1939 : una arqueología de la guerra civil española - Cucarella, José Peinado, (Access archaeology., 2019)
This publication presents the defense of the city of Valencia during the years 1936-1939 under two premises; whether Valencia was strategically bombed and which were the targets. The second premise is whether the city was efficiently organized to protect its civilians.